Leptin −2548 G/A polymorphisms are associated to clinical progression of oral cancer and sensitive to oral tumorization in nonsmoking population - Hung, Wei‐Chen; Tsai, Chiung‐Man; Lin, Chiao‐Wen; Chuang, Chun‐Yi; Yang, Shun‐Fa; Weng, Chia‐Jui (Journal of cellular biochemistry, 2019)
Oral cancer is causally associated with environmental carcinogens, and the susceptibility to carcinogen‐mediated tumorigenesis is proposed to be genotype‐dependent. Leptin (LEP) and leptin receptor (LEPR) both play a crucial role in the mediation of physiological reactions and carcinogenesis and may serve as a candidate biomarker of oral cancer. The current case‐control study aimed to examine the effects of LEP −2548 G/A (rs7799039), LEPR K109R (rs1137100), and LEPR Q223R (rs1137101) single‐nucleotide polymorphisms (SNPs) with or without interacting to environmental carcinogens on the risk for oral squamous cell carcinoma. The SNPs of three genetic allele, from 567 patients with oral cancer and 560 healthy controls in Taiwan were analyzed. The results shown that the patients with polymorphic allele of LEP −2548 have a significant low risk for the development of clinical stage (A/G: adjusted odds ratio [AOR] = 0.670, 95% confidence interval [CI] = 0.454‐0.988, P < 0.05; A/G + G/G: AOR = 0.676, 95% CI = 0.467‐0.978, P < 0.05) compared to patients with ancestral homozygous A/A genotype. In addition, an interesting result was found that the impact of LEP −2548 G/A SNP on oral carcinogenesis in subjects without tobacco consumption is higher than subjects with tobacco consumption. These results suggest that the genetic polymorphism of LEP −2548 G/A (rs7799039), LEPR K109R (rs1137100), and LEPR Q223R (rs1137101) were not associated to the susceptibility of oral cancer; SNP in LEP −2548 G/A showed a poor clinicopathological development of oral cancer; population without tobacco consumption and with polymorphic LEP −2548 G/A gene may significantly increase the risk to have oral cancer.